2006
DOI: 10.1039/b511917k
|View full text |Cite
|
Sign up to set email alerts
|

Chemiluminescence accompanied by the reaction of gold nanoparticles with potassium permanganate

Abstract: It was found that potassium permanganate (KMnO(4)) could react with gold nanoparticles in a strong acid medium to generate particle size-dependent chemiluminescence (CL). For gold nanoparticles with the size of 2.6 or 6.0 nm, the reaction was fast and could produce the excited state Mn(II) with light emission around 640 nm. For gold nanoparticles larger than 6.0 nm, no light emission was observed due to a much slower reaction rate. The CL intensity was found to increase linearly with the concentration of 2.6 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…GNPs have used as catalysts for some CL liquid-phase reactions (Zhang et al, 2005(Zhang et al, , 2006bDuan et al, 2008Duan et al, , 2007Cui et al, 2005a,b;Li et al, 2008). It was found that 6-99-nm GNPs could enhance the luminol-H 2 O 2 CL in different degrees (Zhang et al, 2005).…”
Section: Catalytic Activity Of Gnps On Luminol-h 2 O 2 CL Systemmentioning
confidence: 96%
“…GNPs have used as catalysts for some CL liquid-phase reactions (Zhang et al, 2005(Zhang et al, , 2006bDuan et al, 2008Duan et al, , 2007Cui et al, 2005a,b;Li et al, 2008). It was found that 6-99-nm GNPs could enhance the luminol-H 2 O 2 CL in different degrees (Zhang et al, 2005).…”
Section: Catalytic Activity Of Gnps On Luminol-h 2 O 2 CL Systemmentioning
confidence: 96%
“…Li et al reported the CL of the CdTe/H 2 O 2 system; they studied the directly oxidized CL of CdTe NCs and its size-dependent and surfactant-sensitizing effects in aqueous solution in detail [17]. On the other hand, Cui et al reported the CL of gold nanoparticle in different systems [18][19][20][21][22]. These studies extended the application field of nanoparticles.…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, it has been an expanding area that gold NPs are used as catalyst in the gasphase [13] or liquid-phase reaction [14,15]. Gold NPs have been reported by Cui et al [14,[16][17][18][19] to catalyze different CL systems, and they also have been found to be catalyst in the chemiluminometric determination of NFLX based on its sensitizer effect on the luminol-H 2 O 2 reaction by Wang et al [15]. The results demonstrate that gold NPs-catalyzed CL is of great application potential in analytical chemistry.…”
Section: Norfloxacinmentioning
confidence: 98%